Multi-state Systems with Graduate Failure and Equal Transition Intensities - Mihova, Marija; Popeska, Zaneta (Birkhäuser-Verlag, 2009)
We consider unrecoverable homogeneous multi-state systems with graduate failures, where each component can work at M + 1 linearly ordered levels of performance. The underlying process of failure for each component is a homogeneous Markov process such that the level of performance of one component can change only for one level lower than the observed one, and the failures are independent for different components. We derive the probability distribution of the random vector X, representing the state of the system at the moment of failure and use it for testing the hypothesis of equal transition intensities. Under the assumption that these intensities are equal, we derive the method of moments estimators for probabilities of failure in a given state vector and the intensity of failure. At the end we calculate the reliability function for such systems.
Keywords: Multi-state system, minimal path set, minimal cut set, reliability function, failure intensities